Spatial-temporal assessment of Uaymil Protected Area conservation status using an ecosystem quality index from 2000-2023 - Leider Gemali Coba; Ismael Pat-Aké; Pablo Martínez-Zurimendi; Iván Oros-Ortega; José Francisco López-Toledo; Luis Alberto Lara-Pérez (Revista de Teledetección, 2025)
Protected areas (PAs) are crucial for conserving species and ecosystems but are still susceptible to deforestation and degradation from human and natural causes. The Uaymil Protected Area in Quintana Roo, Mexico, is a key ecological corridor facing deforestation risks due to its location. Due to this the objective of this study was to evaluate the conservation status and analyze the spatial temporal changes within vegetation type of the protected area of flora and fauna “Uaymil” using the Ecosystem Quality Index (EQI). MODIS Terra satellite data for Leaf Area Index (LAI), Gross Primary Productivity (GPP), and Fractional Vegetation Cover (FVC) were used to calculate the annual EQI over 23 years. The results showed a strong integration of LAI, GPP, and FVC into the EQI, improving the model's ability to capture ecosystem quality changes. Significant shifts occurred in 2005, 2011, 2015, and 2023, indicating both degradation and recovery. Lower EQI values were found in mangrove and marsh areas, while forests had higher ecological indicators. Overall, the Uaymil Protected Area maintains high vegetation cover and ecosystem quality, indicating a strong conservation status.